The Addition of Straw Affects the Response of Labile Soil Organic Carbon to the Freezing and Thawing Process - Mengmeng Zhu; Qiang Ma; Shuailin Li; Zhuqing Xia; Changrui Zhou; Yun Gao; Xinhui Zhang; Siyu An; Xiao Jiang; Wantai Yu (Agronomy)
Global warming alters freeze–thaw process frequency and intensity, impacting soil carbon cycles. Four soils from a 12-year straw return experiment were used: S0 (no straw), S1 (low rate of addition), S2 (medium rate), and S3 (high rate). Ten treatments with or without temporary straw addition at different rates were conducted to explore their effects on soil microbial biomass carbon (MBC) and dissolved organic carbon (DOC) under laboratory and field freeze–thaw conditions. Compared to constant temperature, the freeze–thaw process under laboratory conditions reduced MBC (5.79%~29.9%), whereas this trend was mitigated or reversed under field conditions. The alleviating effect of straw addition on the decrease in MBC was greater in S0 than in S1, S2, and S3 by an average of 31.7%. Medium rate straw application (S2 8 t/ha) provided appropriate labile C levels, enhancing microbial activity while keeping DOC low and reducing C loss risk. The results revealed discrepancies in freeze–thaw effects on soil labile OC between laboratory and field conditions, the mitigation of freeze–thaw impacts on MBC by straw addition, and the appropriate straw return rate in Liaohe Plain. Therefore, proper nutrient management can maintain and regulate microbial activity and soil labile C in areas with freeze–thaw cycles.